Development and optimization of pearl millet waste biocomposite ceiling tiles: a waste management approach - Khalid Hussain Ansari; Srikanta Routroy; Rahul Samyal; Shivasheesh Kaushik (Scientific Reports)
Abstract The present study aims to develop and optimize sustainable biocomposite ceiling tiles by partially replacing gypsum with pearl millet waste, combined with Waste Wheat Flour (WWF) and waste paper. It aims to provide a sustainable alternative to conventional gypsum-based product, maintaining thermal insulation and flexural strength. Taguchi method was employed for experimental design, by varying key parameters such as gypsum, Pearl Millet Seed Covering (PMSC), and ceiling tile thickness. The signal-to-noise (S/N) ratio was used to identify the optimal composition and Analysis of Variance (ANOVA) with regression analysis determines the significance of each factor on thermal conductivity and flexural strength. The optimized composition for minimum thermal conductivity (0.065 W/m·K) was identified as 45% PMSC and 10% gypsum at 12 mm thickness. For maximum flexural strength (1.24 MPa), the optimal mix was 55% PMSC and 30% gypsum at 14 mm thickness. The finding underscore the critical influence of gypsum and tile thickness in enhancing material performance. The developed regression models exhibited predictive R2 value of 96.90% for thermal conductivity and 94.44% for flexural strength and an error margin below 3%, confirming the robustness of the approach. This study is original and introduces pearl millet waste biocomposites as eco-friendly alternatives to gypsum ceiling tiles. These tiles hold practical implications in ceiling, partition walls and decorative finishes across various geographic regions, contributing significantly to environmental sustainability and energy-efficient building solutions. Graphical abstract